The Educational Kuznets Curve: A Case of Nepal - Thapa, Surya Bahadur (Tribhuvan University Journal, 2010)
Education is among the basic human needs and one of the components of well being in the modern world. Equal distribution of education is of great interest in public policy analysis. Spending in education represents substantial share of government revenue. The inequality in educational distribution represents large welfare loss. The purposes of this article are three folds. First, it calculates average years of schooling. Second, it estimates educational inequality in terms of standard deviation of schooling. Third, it examines the Educational Kuznets Curve in case of Nepal and answers the question: does it fit? This is quantitative study based on the secondary data collected and published by Central Bureau of Statistics. The study finds that the average years of schooling are increasing over the census years. It stood at 0.125 years in 1952 for all population and 0.245 and 0.019 respectively for males and females. The same data for all population, males and females for the year 2001are 4.385, 5.119, and3.083 years respectively. The data on standard deviation of schooling show that they are all in increasing trend from the census year 1952 to Census Year 2001.With the help of econometric test of both linear and nonlinear quadratic equations, this study concludes that the Educational Kuznets Curves does not exist in Nepal due to very low average years of schooling.